2011
DOI: 10.2169/internalmedicine.50.4430
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Spinal Cord Attacks in a Patient with a Limited Form of Neuromyelitis Optica

Abstract: This report describes the case of a 71-year-old woman with a limited form of neuromyelitis optica (NMO) who had a longitudinally extensive spinal cord lesion from the fourth to the tenth thoracic vertebrae. Up to age 75, she had four subsequent recurrences of the myelitis within the same spinal cord area but with no optic neuritis. Anti-AQP4 antibody was seropositive. Recurrence within the same spinal cord area might be a characteristic clinical finding in NMO spectrum disorders. For such patients, examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Furthermore, the atrophied cord lesions on the follow-up MRI were likely to reflect tissue rarefaction and neuronal loss as a result of intense edema associated with astrocytes injury. Frequent relapses at the same upper spinal cord area in patients with NMOSD were reported as seen in our cases ( 10 , 14 ). Cavitation and frequent relapses at the same upper spinal cord may be characteristic findings of cord lesions in NMOSD.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, the atrophied cord lesions on the follow-up MRI were likely to reflect tissue rarefaction and neuronal loss as a result of intense edema associated with astrocytes injury. Frequent relapses at the same upper spinal cord area in patients with NMOSD were reported as seen in our cases ( 10 , 14 ). Cavitation and frequent relapses at the same upper spinal cord may be characteristic findings of cord lesions in NMOSD.…”
Section: Discussionsupporting
confidence: 80%
“…9 Patients present with signs of white matter dysfunction such as spasticity, hyperreflexia and a positive Babinski sign. [72][73][74] Mild muscle wasting along with pyramidal tract signs, a mixed picture of gray and white matter dysfunction, has been reported. 13 A study of myelitis in SLE revealed that patients with clinical "white matter" myelitis were more likely to fulfill NMO criteria than those with "gray matter" myelitis.…”
Section: Transverse Myelitismentioning
confidence: 99%
“…15,77 Recurrent transverse myelitis, commonly seen in NMO, 30 can occur in the same location in the spinal cord. 74 A progressive course is unusual but still possible. For example, in one report a NMO-IgG seropositive female experienced a 4-month history of progressive quadriplegia and respiratory failure following nausea, vomiting, and hiccupping.…”
Section: Transverse Myelitismentioning
confidence: 99%